Construction of Self-Assembly Based Tunable Absorber: Lightweight, Hydrophobic and Self-Cleaning Properties - Zhou, Zehua; Zhu, Qianqian; Liu, Yue; Zhang, Yan; Jia, Zirui; Wu, Guanglei (Nano-Micro Letters, 2023)
Although multifunctional aerogels are expected to be used in applications such as portable electronic devices, it is still a great challenge to confer multifunctionality to aerogels while maintaining their inherent microstructure. Herein, a simple method is proposed to prepare multifunctional NiCo/C aerogels with excellent electromagnetic wave absorption properties, superhydrophobicity, and self-cleaning by water-induced NiCo-MOF self-assembly. Specifically, the impedance matching of the three-dimensional (3D) structure and the interfacial polarization provided by CoNi/C as well as the defect-induced dipole polarization are the primary contributors to the broadband absorption. As a result, the prepared NiCo/C aerogels have a broadband width of 6.22 GHz at 1.9 mm. Due to the presence of hydrophobic functional groups, CoNi/C aerogels improve the stability in humid environments and obtain hydrophobicity with large contact angles > 140°. This multifunctional aerogel has promising applications in electromagnetic wave absorption, resistance to water or humid environments. Highlights: 1 NiCo/C aerogel was prepared by pyrolysis carbonization self-assembly of NiCo- metal–organic frameworks (MOFs). 2 The assembly mechanism of MOF aerogel was studied by adjusting the ratio of metal ion /BTC. 3 Aerogel combines hydrophobic, lightweight, self-cleaning, and electromagnetic wave absorption properties.